Edaphic factors modulating phosphorus availability in lowland rice systems, Nigeria - Mesele, S.A.; Ajiboye, G.A.; Talbot, J. (Informa UK Limited, 2024)
The low rice production level in Africa is attributed to poor soil fertility despite the potential for rice cultivation in the inland valleys. This study was conducted to evaluate soil characteristics in some lowlands that have been continuously and intensively used for rice production for over two decades in southwestern Nigeria. Soil physical, chemical, and mineralogical properties, as well as phosphorus sorption characteristics, were assessed in soil samples collected from diagnostic horizons of profiles in six benchmark soils. The results show kaolinite, quartz, potassium(K)-feldspars, and mixed-layered smectite as the predominant minerals. The iron oxide fractions indicate that the soils are at varying degrees of development where the soils at the advanced stage of development are predominantly rich in kaolinite and quartz with a high concentration of total pedogenic iron oxide and generally low in soil fertility. Soil phosphorus buffering capacity is low and varies inversely with pH, confirming the deficiency of phosphorus at low pH. Short-range-order (SRO) iron (Fe) oxides show a strong affinity for phosphorus and this is stronger at lower soil horizons and mediated by some redoxomorphic reactions. The SRO iron oxide concentration has more influence on phosphorus retention in soils rather than the absolute concentration of iron oxides. The study concludes that SRO Fe oxides and soil pH are the major edaphic factors playing a prominent role in phosphorus retention and availability in the wetland soils rather than the clay minerals.